The Effect of Consumer Satisfaction and Trust on Loyalty Through Brand Image as Mediation: Study on Online Travel Agent Tiket.com consumers - Grimonia, Raissa; Rohman, Fatchur; Suryadi, Nanang (Devotion : Journal of Research and Community Service, 2023)
This study examines the effect of consumer satisfaction and trust on loyalty through brand image as mediation among consumers of the online travel agent Tiket.com. The research aims to understand the relationship between consumer satisfaction and trust, brand image, and loyalty in the context of online travel agents. The study utilizes a quantitative research approach and collects data through a survey questionnaire administered to Tiket.com consumers. The findings of this research contribute to the understanding of the factors influencing consumer loyalty in the online travel industry. The results highlight the importance of consumer satisfaction and trust in shaping brand image and ultimately influencing consumer loyalty. The implications of these findings for online travel agents and recommendations for future research are discussed.